Acute aerobic exercise enhances associative learning in regular exercisers but not in non-regular exercisers - Gultig, Kayleigh D.; Boele, Cornelis P.; Roggeveen, Lotte E. M.; Soong, Ting Fang; Koekkoek, Sebastiaan K. E.; De Zeeuw, Chris I.; Boele, Henk-Jan (Frontiers in Behavioral Neuroscience, 2025)
IntroductionPhysical exercise has repeatedly been reported to have advantageous effects on brain functions, including learning and memory formation. However, objective tools to measure such effects are often lacking. Eyeblink conditioning is a well-characterized method for studying the neural basis of associative learning. As such, this paradigm has potential as a tool to assess to what extent exercise affects one of the most basic forms of learning. Until recently, however, using this paradigm for testing human subjects in their daily life was technically challenging. As a consequence, no studies have investigated how exercise affects eyeblink conditioning in humans. Here we hypothesize that acute aerobic exercise is associated with improved performance in eyeblink conditioning. Furthermore, we explored whether the effects of exercise differed for people engaging in regular exercise versus those who were not.MethodsWe conducted a case–control study using a smartphone-based platform for conducting neurometric eyeblink conditioning in healthy adults aged between 18 and 40 years (n = 36). Groups were matched on age, sex, and education level. Our primary outcome measures included the amplitude and timing of conditioned eyelid responses over the course of eyeblink training. As a secondary measure, we studied the amplitude of the unconditioned responses.ResultsAcute exercise significantly enhanced the acquisition of conditioned eyelid responses; however, this effect was only true for regularly exercising individuals. No statistically significant effects were established for timing of the conditioned responses and amplitude of the unconditioned responses.DiscussionThis study highlights a facilitative role of acute aerobic exercise in associative learning and emphasizes the importance of accounting for long-term exercise habits when investigating the acute effects of exercise on brain functioning.